Multi-element analysis of milk by ICP-oa-TOF-MS after precipitation of calcium and proteins by oxalic and nitric acid - Husáková, Lenka; Urbanová, Iva; Šrámková, Jitka; Konečná, Michaela; Bohuslavová, Jana (Talanta, 2013)
In this work a simple technique employing oxalic and nitric acid to cow's milk samples prior to analysis by inductively coupled plasma orthogonal acceleration time-of-flight mass spectrometry (ICP-oa-TOF-MS) was introduced. After the precipitation of calcium and proteins via oxalic and nitric acid, respectively, the resulting liquid phase was aspirated with a concentric glass nebulizer for ICP-TOF-MS determination of trace elements. Precipitation of proteins is essential for better separation of solid and liquid phase of modified samples. Separation of calcium as a precipitated non-soluble oxalate enables the elimination of spectral interferences originating from different calcium containing species like (40)Ca(35)Cl(+), (40)Ca(37)Cl(+), (43)Ca(16)O(+), (40)Ca(18)O(+), (44)Ca(16)O(+), (43)Ca(16)O(1)H(+) onto the determination of As, Se, Co and Ni whose assay is more difficult when using conventional quadrupole instruments. High detection capability is further an advantage as the approach enables the analysis without dilution. The methodology may serve, in addition, for a fast and sensitive determination of some other elements. After that, direct, reliable and simultaneous determination of 16 elements (Li, Be, B, V, Cr, Mn, Ni, Co, Ga, As, Se, Mo, Sn, Sb, Cs, Tl) at trace and ultra-trace levels in milk can be performed under optimum instrumental conditions and by using Rh as an internal standard. Accuracy and precision was assessed by measuring NCS ZC73015 milk powder control standard, yielding results in agreement with certified values and RSD <10%. The accuracy was also checked by comparison of the results of the proposed method with those found by a method based on a microwave-assisted digestion of real samples.
Keywords: Calcium; Spectrophotometry, Atomic; Sensitivity and Specificity; senzitivita a specificita; Cations, Divalent; Nitric Acid; referenční standardy; mléčné bílkoviny; kyselina oxalová; vápník; kyselina dusičná; stopové prvky; zvířata; kationty dvojmocné; Reference Standards; spektrometrie hmotnostní - ionizace laserem za účasti matrice; Milk; Trace Elements; Milk Proteins; Animals; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Oxalic Acid; mléko; chemická precipitace; spektrofotometrie atomová; Chemical Precipitation